Quality of Basic Education Services in Donggala Regency, Central Sulawesi Province - Irwan Waris (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2022)
The purpose of this research is to find out what the true picture is of the quality of basic education services in Donggala Regency, Central Sulawesi Province, and what variables impact it. To answer these problems, qualitative approaches with a phenomenological perspective were used. After the research was completed, the quality of basic education services in Donggala Regency did not meet community expectations owing to a lack of management based on elements such as dependability, responsiveness, assurance, empathy, and tangibles. The poor commitment of the local government, particularly the officials of the Donggala Regency Education Office, to completing different areas of establishing the quality of education services is one of the causes influencing it. Furthermore, the community's and business/industry world's lack of involvement has an impact. This study presents a number of suggestions/recommendations that the Donggala Regency government, Donggala Regency Education Office, and stakeholders in the field of basic education development, particularly basic education services, are expected to use to improve the quality of basic education services.